A Starring Role for Microglia in Brain Sex Differences. (June 2015) - Lenz, Kathryn M.; McCarthy, Margaret M.
Microglia, the resident innate immune cells in the brain, have long been understood to be crucial to maintenance in the nervous system, by clearing debris, monitoring for infiltration of infectious agents, and mediating the brain's inflammatory and repair response to traumatic injury, stroke, or neurodegeneration. A wave of new research has shown that microglia are also active players in many basic processes in the healthy brain, including cell proliferation, synaptic connectivity, and physiology. Microglia, both in their capacity as phagocytic cells and via secretion of many neuroactive molecules, including cytokines and growth factors, play a central role in early brain development, including sexual differentiation of the brain. In this review, we present the vast roles microglia play in normal brain development and how perturbations in the normal neuroimmune environment during development may contribute to the etiology of brain-based disorders. There are notable differences between microglia and neuroimmune signaling in the male and female brain throughout the life span, and these differences may contribute to the vast differences in the incidence of neuropsychiatric and neurological disorders between males and females.